Understanding of pragmatism and Islamic perspective: a case study of University Kuala Lumpur students / Sakinah Munarwarrah Hashim - Hashim, Sakinah Munarwarrah (Academy of Contemporary Islamic Studies (ACIS), 2021)
This paper discusses the ideology of pragmatism. The research was conducted at one of the UniKL branch institutes, the British Malaysian Institute in Gombak. The British Malaysian Institute majorly offers engineering courses with expertise in electrical, electronics and medical electronic engineering. This study aims at analysing the UniKL students’ understanding of pragmatism ideology and how their understanding shapes their thinking and action. This article highlighted some features of pragmatism by referring to the one of the famous pioneers of pragmatism, Williams James. A set of questionnaire was instrumented for collecting data from the respondents on their thought regarding the ideology of pragmatism. This ideology has changed the lifestyle of people especially for Muslim. This is because people believe that this ideology is more practical in solving problems consequently some of this ideology is not suitable for Muslim. The result of this study revealed that respondents did not have much understanding about this ideology due to lack of Islamic principal. Therefore, it is suggested that learning institutions need to instil better understanding of pragmatism ideology among students and responsible for educators to educate students properly in order to protect their faith especially among the Muslim students.